Bonding in Diborane–Metal Complexes: A Quantum‐Chemical and Experimental Study of Complexes Featuring Early and Late Transition Metals. Issue 23 (9th April 2013) - Wagner, Arne; Kaifer, Elisabeth; Himmel, Hans‐Jörg
Abstract The coordination chemistry of the doubly base‐stabilised diborane(4), [HB(hpp)]2 (hpp=1, 3, 4, 6, 7, 8‐hexahydro‐2H‐pyrimido‐[1, 2‐a]pyrimidinate), was extended by the synthesis of new late transition‐metal complexes containing CuI and RhI fragments. A detailed experimental study was conducted and quantum‐chemical calculations on the metal–ligand bonding interactions for [HB(hpp)]2 complexes of Group 6, 9, 11 and 12 metals revealed the dominant BHM interactions in the case of early transition‐metal fragments, whereas the BBM bonding prevails in the case of the late d‐block compounds. These findings support the experimental results as reflected by the IR and NMR spectroscopic parameters of the investigated compounds. DFT calculations on [MeB(hpp)]2 and model reactions between [B2H4⋅2NMe3] and [Rh(μ‐Cl)(C2H4)2] showed that the bicyclic guanidinate allows in principle for an oxidative addition of the BB bond. However, the formation of σ‐complexes is thermodynamically favoured. The results point to the selective BH or BB bond‐activation of diborane compounds by complexation, depending on the chosen transition‐metal fragment.